Working with clients engaging in recurrent suicidal behavior: impacts on community mental health practitioners - Megan Collisson; Jacinta Hawgood (Frontiers in Public Health)
BackgroundPractitioners have reported negative emotional impacts following client suicide. However, there is a paucity of literature exploring the impacts of working with clients engaging in suicidal behavior and on the impacts of repeat exposure to these events from the perspectives of practitioners.AimThis qualitative study aimed to investigate the perceived impacts of working with clients engaging in recurrent suicidal behavior on Australian community mental health practitioners.MethodA phenomenological approach was utilized to explore the experiences of practitioners working with this client cohort; the impacts on them, the supports and resources used to sustain them and those perceived as necessary to increase the future sustainability of this important workforce. Eight practitioners were recruited via criterion snowball sampling to participate in semi-structured interviews up to a maximum of 45 min duration.ResultsParticipants were comprised of mental health clinicians (N = 6) and psychosocial support workers (N = 2) in community mental health settings. Thematic analysis revealed six major themes and several sub-themes. Practitioners experienced diversity of challenges and a diversity of emotional and psychological responses, along with impacts on their personal and professional lives. In response to these impacts, they reported positive experiences with individual supervision, debriefing and secondary consultation from specialist services, although access to these supports varied. Further, they highlighted the impact of systemic issues on their work with these clients including workforce shortages, staff turnover and client lack of access to needed supports (such as psychologists, psychosocial support workers and specialist services).ConclusionWhile workplaces have a role to play in providing supports to reduce impacts on workers, further systemic work is required to increase sustainability of this workforce.